Pembuatan Yogurt sebagai Upaya Ketahanan Pangan dan Gizi di Panti Asuhan Sunan Ampel Kota Malang - Devi, Hilda Mazarina; Rosdiana, Yanti; Widyastuti, Fikka Kartika; Sujana, Indra Ahmad; Kitu, Graccelya Angel (Prosiding Seminar Kesehatan Nasional, 2024)
A social welfare institution serves as a substitute for parents or guardians in fulfilling the physical, mental, and social needs of children under its care, while also introducing activities that support economic independence. A community service initiative, in the form of a series of workshops on the production of YOSS (Healthy Squeezable Yogurt), has been designed as an effort to empower partnerships that enhance both the health and economic strength of the institution. This community service program is conducted over a one-year period, with active mentoring provided for three months, from July to Seotember 2024, targeting the caregivers and 55 residents at Sunan Ampel Orphanage (PASA) in Malang City. The mentoring covers various aspects, including production, consumption, packaging, and marketing. PASA possesses significant potential for developing this enterprise, supported by a young workforce and available basic facilities. However, challenges remain in improving production quality, particularly in maintaining the sterility of equipment and products. The production of YOSS has the potential to be further developed into a flagship product through expanded marketing and distribution efforts.